IMPLEMENTATION OF HAFIZ QURAN EDUCATION IN THE DEVELOPMENT OF CHARACTER IN DAARUL HUFFADZ ISLAMIC BOARDING SCHOOL MEDAN, SERDANG BEDAGAI REGENCY - Dianto Dianto (Proceeding International Seminar of Islamic Studies, 2022)
As Muslims, we already understand that the Qur'an is a guide and guide for the life of the people of the Seasons so that they are always on the straight and right path. To overcome the declining morality and character of children and away from the teachings of Islam, a substance that is very useful is needed to create a generation of children who are faithful, moral and knowledgeable. So what we have to do especially for parents is to educate them at the Daarul Huffadz Islamic Boarding School Medan, Serdang Bedagai Regency. The specific target to be achieved from this research is to provide input and encourage students to improve their morals so that they can become the next generation of a nation of faith and noble character. The method used in this study is a qualitative method, using a phenomenological approach and type of research. Data collection used in the study were interviews and observations. Furthermore, the activity plan is carried out through stages consisting of: data collection as well as data reduction, data presentation and conclusion drawing and data verification. The results of the study explained that the students at the Daarul Huffadz Islamic Boarding School Medan, Serdang Bedagai Regency, God willing, all of them have the ability to memorize the Quran and have noble character.Keywords: Implementation, Hafiz Quran and Morals.